The implementation of Islamic spirituality and Islamic social responsibility on Islamic banking employees, its implication towards workplace deviance - Siswanto, Siswanto (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2018)
This study aims to analyze the effects of Islamic spirituality and Islamic social responsibility on workplace deviance. Series of data analysis techniques have been projected to achieve the goal oriented.Â However, the techniques include descriptive statistical analysis through cross tabulation, comparative test and Partial Least Square (PLS) analysis. The results indicate that: 1) the characteristic of employee age determine the difference of Islamic spirituality implementation, 2) the difference of employee age determines the difference ofÂ Islamic social responsibility implementation, 3) the differences of biographical characteristics of Islamic banking employees covering gender differences, marital status, and age differences do not determine implementation of workplace deviance, 4) Implementation of Islamic piety concept which includes Islamic spirituality or personal piety, and social responsibility or social piety affect deviant behavior in the workplace. Social piety can reduce deviant behavior in the workplace. While personal piety is not able to reduce deviant behavior in the workplace.Keywords: Islamic spirituality, Islamic social responsibility, Workplace deviance